2012
DOI: 10.2307/41410416
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm IT Capability Profiles and Communications for Cocreating Relational Value: Evidence from the Logistics Industry

Abstract: it-capability-profiles-and-communications-for-cocreating-relational-valueevidence-from-the-logistics-industry.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(140 citation statements)
references
References 130 publications
0
137
0
3
Order By: Relevance
“…As noted above, IT capability is an important class of organizational capability for governing a business well and adding value to its assets (Bharadwaj, 2000;Chi et al, 2010;Pavlou & El Sawy, 2010;Rai & Tang, 2010;Lu & Ramamurthy, 2011;Tanriverdi & Uysal, 2011;Rai et al, 2012). The logic of the market for corporate control perspective suggests that the differences in IT capabilities between an acquirer and its target could drive M&A transactions over and beyond the effects of previously studied drivers of M&A activity and M&A performance (e.g., merger waves, deal, target, and acquirer characteristics).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
See 1 more Smart Citation
“…As noted above, IT capability is an important class of organizational capability for governing a business well and adding value to its assets (Bharadwaj, 2000;Chi et al, 2010;Pavlou & El Sawy, 2010;Rai & Tang, 2010;Lu & Ramamurthy, 2011;Tanriverdi & Uysal, 2011;Rai et al, 2012). The logic of the market for corporate control perspective suggests that the differences in IT capabilities between an acquirer and its target could drive M&A transactions over and beyond the effects of previously studied drivers of M&A activity and M&A performance (e.g., merger waves, deal, target, and acquirer characteristics).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…IT capabilities are an important class of organizational capabilities. Business value of IT literature has shown that IT capabilities enable firms to integrate their internal business units, newly acquired businesses, and achieve cross-business synergies (Tanriverdi & Uysal, 2011); connect with external business partners, exchange physical goods, information, and finances with them and create business value in interorganizational relationships (Rai & Tang, 2010;Rai et al, 2012); increase organizational agility (Lu & Ramamurthy, 2011); proactively sense and respond to competitive dynamics (Chi et al, 2010); improvise in turbulent competitive environments and achieve competitive advantages (Pavlou & El Sawy, 2010). Thus, IT capability asymmetries between acquirer and target are likely to affect how the merger creates or destroys shareholder wealth.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, may lead to a bias in assessment of value impacts inflating the value estimate of a firm's own ITs. Evidence of value creation by contemporary enterprise technologies, such as the RosettaNet's Partner Interface Processes (PIPs) and other ITs, is also of significance to research examining role of IT in contemporary supply chains Banker et al 2006;Rai et al 2012;Malhotra et al 2005). In the context of supply chains it is well known that competition is now between the network of partners, and not individual firms.…”
Section: Contributionsmentioning
confidence: 97%
“…requires that the firm uses its own IT systems in synch with complementary inputs from IT systems of partner organizations. As Rai et al (2012) show, even though large firms (such as, Hewlett Packard (HP) and United Parcel Service (UPS)) co-create value, value co-creation depends on complementary interfirm communications between a supplier and its buyer firms. In general, a firm with greater IT intensity relies more on digitized processes.…”
Section: Effects Of It Intensity On Value Co-creation and Appropriationmentioning
confidence: 99%
“…Rai et al 2006;Devaraj, Krajewski, and Wei 2007;Sanders 2007;Sanders 2008;Rai et al 2012;Tenhiälä and Helkiö forthcoming). Scholars have investigated a mixture of applications supporting supply chain processes (Clark and Lee 2000;McAfee 2002;Kent and Mentzer 2003;Ranganathan, Dhaliwal, and Teo 2004;Jin 2006;Wu et al 2006), which might be categorised into internal, supply-side and customer-side applications (Barua et al 2004;Subramani 2004;Devaraj, Krajewski, and Wei 2007).…”
Section: Introductionmentioning
confidence: 99%